Answer:
k =
![(u^2y-x)/(u^2-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rl6hxvqjw7m7ou3381co9pyrc3ez5dgevm.png)
Explanation:
Given
u =
( square both sides )
u² =
← multiply both sides by (k - y)
u²(k - y) = k - x ← distribute left side
u²k - u²y = k - x ( subtract k from both sides )
u²k - k - u²y = - x ( add u²y to both sides )
u²k - k = u²y - x ← factor out k from each term on the left side
k(u² - 1) = u²y - x ← divide both sides by (u² - 1)
k =
![(u^2y-x)/(u^2-1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/rl6hxvqjw7m7ou3381co9pyrc3ez5dgevm.png)